(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
There are different security dangers and assaults which can impact the data transmission through the wired and wireless communication networks. By carrying out the secure and safe system for privacy and information reliability for making sure of safe information transmission, the problem can be solved. Digital images are quite well-known due to the fact of their frequency on Web from every varying carrier file format. Through Steganography, it is possible to conceal that there is a communication by concealing the information under other information. Numerous kinds of steganography methods can be found where all of them have their pros and cons. Hashing algorithm, steganography methods Data encryption can be helpful in securing information exchange through communication sources. It is possible to categorize cryptographic algorithms and protocol as symmetric and asymmetric. Shared key in the symmetric method can be helpful in privacy service as the blocks or streams of plain text of all sizes are transmitted to cipher text that cannot be read. Current Literature is examined here in the research study which is about improving security through Hash -Crypto- Steganography so the communication source can be safe and sound.